Pendampingan Optimalisasi Penilaian Otentik dalam Pembelajaran Bahasa Indonesia Tingkat SMK di Kota Binjai - M Joharis; Mara Untung Ritonga; Savitri Rahmadany; Rizki Fadila Nasution (Jurnal Masyarakat Indonesia (Jumas), 2024)
This community service (PKM) aimed to optimizing authentic assessments in Indonesian language learning at vocational high school level in Binjai city. This community service activity aims to improve the competence of teachers in designing and implementing authentic assessments in accordance with skills in vocational schools. Authentic assessment is an assessment that is in accordance with the demands of contextual learning. Authentic assessment is not only used to assess student learning outcomes, but also the learning process carried out. The purpose of authentic assessment is to measure various skills in various contexts that reflect real-world situations where these skills are used. Authentic assessment can also be used to ensure true information about student abilities or competencies. This PKM activity is carried out through several methods, namely: 1) Preparation stage, 2) Implementation stage, 3) Evaluation stage. The results of this PKM are: 1) Training participants understand the basic concept of authentic assessment in Indonesian language learning based on the Merdeka Curriculum in SMK, 2) Training participants can design and design authentic assessments in Indonesian language learning based on the Independent Curriculum in SMK, 3) Training participants can apply authentic assessments in Indonesian language learning based on the Merdeka Curriculum in SMK in the evaluation process of student learning outcomes. This study is expected to help teachers become competent and professional teachers in teaching and also competent and professional in designing and implementing authentic assessments in Indonesian language learning according to learning needs in SMK.